Pengembangan E-Book Berbantuan Canva Materi Majas Metafora Siswa Kelas IV SD Negeri 1 Jepun Kabupaten Tulungagung - Khoridah, Khoridah; Sari, Eka Yuliana; Syafi’ah, Rohmatus (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is motivated by the low understanding of fourth-grade students of SD Negeri 1 Jepun, Tulungagung Regency regarding the material of metaphorical figures of speech. The results of initial identification showed that 13 out of 27 students scored below the Minimum Competency (KKM). This condition indicates the need for learning media that are more appropriate to the characteristics of students because learning is still dominated by lecture methods and the use of conventional media. This study aims to describe the development process, validity, and practicality of Canva-assisted e-books on metaphorical figures of speech. The study used a research and development (R&D) method with the ADDIE model which includes the Analysis stage to identify needs, Design to design the structure and content of the product, Development to develop and validate the e-book, Implementation through small and large group trials, and Evaluation to improve the product based on validation results and user responses. The research subjects consisted of 5 students in the small group trial and 27 students in the large group trial. The validation results from media, materials, and language experts reached 90%, 92%, and 94%, respectively, categorized as very valid. Practicality, based on teacher and student responses, reached 94% and 92%, respectively, categorized as very practical.